PENGARUH MURABAHAH, MUSYARAKAH, MUDHARABAH, DAN IJARAH TERHADAP PROFITABILITAS BANK UMUM SYARIAH DI INDONESIA - Faiz Nurfajri (Monex: Journal of Accounting Research, 2019)
The aim of this study was to examine the effect of Murabaha, Musyaraka, Mudharaba, and Ijara on Profitability on all Sharia General Bank listed in Otoritas Jasa Keuangan (OJK) period June 2015 – June 2018. The sampling in this study of 13 banks listed in Otoritas Jasa Keuangan period June 2015 – June 2018 with purposive sampling method. Data obtained from the company’s financial statements that have been publication. The number of samples was obtained from 13 companies with total 91 sample. After eliminating the outlier data, which eventually resulted 66 observations that ready to be analyzed and tested. The analysis technique that used in this study is multiple linear regression with a significance level of 5%. The results in this study indicates that (1) Murabaha has significant effect on Profitability, (2) Musyaraka has significant effect on Profitability, (3) Mudharaba has significant effect on Profitability, and (4) Ijara has not significant effect on profitability. Ijara was the only variable in this research that has not significant effect on profitability because the proportion of ijara is the smallest financing of all.